Prognostic evaluation of COPD patients: GOLD 2011 versus BODE and the COPD comorbidity index COTE. Issue 9 (26th June 2014) - de Torres, Juan P; Casanova, Ciro; Marín, Jose M; Pinto-Plata, Victor; Divo, Miguel; Zulueta, Javier J; Berto, Juan; Zagaceta, Jorge; Sanchez-Salcedo, Pablo; Cabrera, Carlos; Carrizo, Santiago; Cote, Claudia; et al.
Abstract : Background: The Global Obstructive Lung Disease (GOLD) 2011 revision recommends the multidimensional assessment of COPD including comorbidities and has developed a disease categories system (ABCD) attempting to implement this strategy. The added value provided by quantifying comorbidities and integrating them to multidimensional indices has not been explored. Objective: Compare the prognostic value of the GOLD ABCD categories versus the BMI, Obstruction, Dyspnea, Exercise (BODE) index, and explore the added prognostic value of comorbidities evaluation to this multidimensional assessment. Methods: From the patients who have been enrolled in the BODE study, we selected the most recent ones who had the available information needed to classify them by the ABCD GOLD categories. Cox proportional hazards ratios for all-cause mortality were performed for GOLD categories and BODE index. The added value of the comorbidity Copd cO-morbidity TEst (COTE) index was also explored using receiver operating curves (ROC) values. Results: 707 patients were followed for 50±30 months including all degrees of airway limitation and BODE index severity. ABCD GOLD predicted global mortality (HR: 1.47; 95% CI 1.28 to 1.70) as did the BODE index (HR: 2.02; 95% CI 1.76 to 2.31). Area under the curve (AUC) of ROC for ABCD GOLD was 0.68; (95% CI 0.64 to 0.73) while for the BODE index was 0.71 (95% CI 0.67 to 0.76). The C statistics value was significantly higher for the observed difference. Adding the COTE index to the BODE index improved its AUC to 0.81 (95% CI 0.77 to 0.85), (χ 2 =40.28, p<0.001). Conclusions: In this population of COPD patients, the BODE index had a better survival prediction than the ABCD GOLD categories. Adding the COTE to the BODE index was complimentary and significantly improved outcome prediction.